Solvent-free synthesis of cyclic polycaprolactone catalysed by MOF-derived ZnO/NCs catalysts. (5th January 2021) - Naz, Farah; Ciprian, Matteo; Mousavi, Bibimaryam; Chaemchuen, Somboon; Zhu, Meifang; Yan, Shilin; Verpoort, Francis
Graphical abstract: Highlights: ZnO dispersed in an N-doped carbon matrix (ZnO/NCs) was derived from thermal treatment of Zn-DABCO. The ZnO/NCs catalysts showed excellent activity towards the polymerization of ε-caprolactone. The acid and basic sites present in the ZnO/NCs co-operatively catalyze the polymerization. The ZnO/NCs catalyst produces high molecular weight cyclic polycaprolactone (c-PCL). The catalyst retained its stability and activity after being used for at least seven cycles. Abstract: For the first time, ZnO dispersed in an N-doped carbon matrix (ZnO/NCs) was derived from the controlled thermal treatment of Zn-DABCO and utilized as a robust heterogeneous catalyst for the polymerization of ε-caprolactone. The as-prepared ZnO/NCs catalysts were characterized using TEM, SEM, Raman spectroscopy, XPS, XRD, TPD and N2 adsorption. The catalyst displayed excellent activity towards the ε-caprolactone polymerization reaction, following the trend, Zn/NC-1000 < Zn/NC-800 < Zn/NC-600. The polymerization was catalyzed co-operatively by both acid and basic sites present in the ZnO/NCs, leading to high molecular weight cyclic polycaprolactone (c-PCL). Furthermore, the catalyst retained its stability and activity after being used for seven cycles without showing any significant loss in performance.